2021
DOI: 10.1016/s1473-3099(21)00019-0
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and validation of clinical phenotypes with prognostic implications in patients admitted to hospital with COVID-19: a multicentre cohort study

Abstract: Background The clinical presentation of COVID-19 in patients admitted to hospital is heterogeneous. We aimed to determine whether clinical phenotypes of patients with COVID-19 can be derived from clinical data, to assess the reproducibility of these phenotypes and correlation with prognosis, and to derive and validate a simplified probabilistic model for phenotype assignment. Phenotype identification was not primarily intended as a predictive tool for mortality. MethodsIn this study, we used data from two coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
77
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(105 citation statements)
references
References 17 publications
8
77
0
7
Order By: Relevance
“…By contrast, less focus has been placed on patient profiles involving the entire combination of symptoms, especially in ICU, or biological measurements such as cytokine levels and their relationships with the outcome [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, less focus has been placed on patient profiles involving the entire combination of symptoms, especially in ICU, or biological measurements such as cytokine levels and their relationships with the outcome [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Our data also suggest that XAV-19 has an antiviral effect in vivo , as the numerical reduction of nasopharyngeal viral loads was greater with XAV-19 than with placebo, although our analysis was exploratory and performed on a limited number of patients. Studies have shown that symptom onset is not a sufficient predictor of the viral load in respiratory secretions, as high viral loads might persist for 2 weeks, nor is it a sufficient predictor of individual innate immune responses or the ability of the immune response to control ongoing viral replication ( 12 14 ). Thus, although a maximal benefit of any antiviral therapy, either specific antiviral or neutralizing antibodies, is expected when treatment is started earlier in the illness, the benefit could also persist in treated patients with a longer duration of symptoms, as demonstrated with remdesivir ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…To reduce the confounding effects of several conditions on the outcome a 1:1 ratio Propensity Score Matching (PSM) was applied to match treated and untreated patients without replacement in the survival analysis. Variables previously associated with COVID-19 mortality, such as: age, sex, pneumonia/flu vaccination status, hypertension, chronic obstructive pulmonary disease, diabetes, obesity, chronic pulmonary and digestive diseases, asthma, chronic heart diseases and cancer were included [28] (Table 2). The propensity scores have been estimated by means of a Generalized Additive Model with a logit as the link function while the matching, to ensure a similar distribution of all the covariates across treatment groups, has been done using the nearest neighbor matching modality [29].…”
Section: Methodsmentioning
confidence: 99%